2009
DOI: 10.3155/1047-3289.59.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Clean Air Status and Trends Network Nitrate and Nitric Acid Measurements with Data from Other Monitoring Programs

Abstract: The U.S. Environmental Protection Agency Clean Air Status and Trends Network (CASTNET) utilizes an open-face filter pack system to measure concentrations of atmospheric sulfur and nitrogen species. Concentration data for nitrogen species measured with filter pack systems sometimes deviate from data collected by other measurement systems used to measure the same species. The nature of these differences suggests that more than one sampling mechanism or atmospheric process is involved. The study presented here ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…CASTNET collects weekly integrated open‐air samples for the analysis of atmospheric sulfur and nitrogen species. Comparisons of IMPROVE and CASTNET data at collocated sites have been the focus of several studies [e.g., Ames and Malm , 2001; Malm et al , 2002; Sickels and Shadwick , 2008; Lavery et al , 2009] and generally suggest good agreement for sulfate ion concentrations, less so for nitrate ion concentrations [ Lavery et al , 2009]. Using weekly precipitation samples collected by the NADP, Lehmann and Gay [2011] report spatial and temporal trends for sulfate and nitrate concentrations in precipitation that suggest similar spatial patterns to particulate concentrations in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…CASTNET collects weekly integrated open‐air samples for the analysis of atmospheric sulfur and nitrogen species. Comparisons of IMPROVE and CASTNET data at collocated sites have been the focus of several studies [e.g., Ames and Malm , 2001; Malm et al , 2002; Sickels and Shadwick , 2008; Lavery et al , 2009] and generally suggest good agreement for sulfate ion concentrations, less so for nitrate ion concentrations [ Lavery et al , 2009]. Using weekly precipitation samples collected by the NADP, Lehmann and Gay [2011] report spatial and temporal trends for sulfate and nitrate concentrations in precipitation that suggest similar spatial patterns to particulate concentrations in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-model studies have shown variations in global BC burden and lifetime of up to a factor of 4-5 (Lee et al, 2013;Samset et al, 2014). Previous comparisons of modeled BC distributions with observations have also pointed to two distinct features common to many models: an overestimation of high-altitude concentrations at low latitudes to midlatitudes and discrepancies in the magnitude and seasonal cycle of high-latitude surface concentrations (e.g., Eckhardt et al, 2015;Lee et al, 2013;Samset et al, 2014;. As accurate representation of the observed aerosol distributions in global models is crucial for confidence in estimates of RF, these issues emphasize the need for broad and up-to-date evaluation of model performance.…”
mentioning
confidence: 99%
“…CASTNET uses an open-face system to collect aerosols on Teflon filters for approximately 1 week for each filter (Lavery et al, 2009). In comparison, the Chemical Speciation Monitoring Network (CSN), which also samples the continental United States and collects the aerosols on nylon or Teflon filters, a denuder is used to scrub gas-phase ammonia to minimize interaction of ammonia with acidic aerosols on filters (Solomon et al, 2000(Solomon et al, , 2014.…”
Section: Impacts Of Ammonia Uptake On Acidic Filtersmentioning
confidence: 99%